Kako nastane knjiga - pouk v četrtem razredu o nastanku in zgradbi knjige - Škrlj, Gregor (Šolska knjižnica, 2014)
The paper presents teaching about making of books, their structure, component parts and ways of motivating the pupils for classical printed books as authored work or a product with content. The paper describes a presentation of various definitions of a book and an explanation about which experts are involved in the process of making a book. It uses picture material to demonstrate the making of different books by skilled pupils during classes.
Keywords: izdelava; knjige; metodika; osnovne šole; pouk; učne metode; založništvo